2018
DOI: 10.1088/1361-6587/aadd69
|View full text |Cite
|
Sign up to set email alerts
|

Plasma confinement by moving multiple mirrors

Abstract: The achievable gain in magnetic mirrors fusion machines is limited by particles and energy flux through the mirrors. The moving multiple mirrors (MMM) concept is based on many mirror coils at each end of the trap, synchronized in sequence to generate magnetic mirror that moves towards the centre of the trap. Particles escaping from the main cell are scattered out of the loss-cone in the MMM sections and propelled back inside by the magnetic wave. Analytical optimization of the MMM parameters for a conceptual f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…That proposal renewed the idea of a plasma flow control with moving magnetic mirrors [10]. Recent analysis in [11] have shown that the modulation of the guiding magnetic field travelling in the laboratory reference frame may be achievable, but presumably restricts the usage of the superconducting magnetic system due to the mechanical stresses and coil quenching. Therefore, an emulation of the moving magnetic mirrors by the stationary magnetic field is still of sufficient interest.…”
Section: Introductionmentioning
confidence: 99%
“…That proposal renewed the idea of a plasma flow control with moving magnetic mirrors [10]. Recent analysis in [11] have shown that the modulation of the guiding magnetic field travelling in the laboratory reference frame may be achievable, but presumably restricts the usage of the superconducting magnetic system due to the mechanical stresses and coil quenching. Therefore, an emulation of the moving magnetic mirrors by the stationary magnetic field is still of sufficient interest.…”
Section: Introductionmentioning
confidence: 99%
“…GOL-NB is the representative of classical multiple-mirror configurations, which provide slowing down plasma expansion along the axis due to momentum transfer at collisional interaction of transiting and locally-trapped populations. Recently, an old idea of active multiple-mirror confinement [41] was reconsidered in two different approaches: with moving magnetic mirrors [42] and with rotating plasma in a helical mirror configuration [43,44]. Modular design of GOL-NB allows incorporation of an active section of a limited length into the magnetic structure that will expand the device capabilities when the main scientific goal will be achieved first.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…As a concluding remark, we note that even in the optimal regime and in the cooling scenarios, where the flux is minimal, the improvement in confinement time due to MM is not enough for fusion. Therefore, to enhance confinement, a future study may consider more advanced control tools such as moving magnetic mirrors 34 and external RF fields.…”
Section: Discussionmentioning
confidence: 99%
“…For ideal gases, the adiabatic cooling law is T ∝ n γ−1 where γ = (d + 2) /d and d is number of degrees of freedom. 34 Plugging this relation in the MFP gives λ ∝ n 2γ−3 in the cooling scenario. Hence, the MFP will decrease on expansion for systems with d < 4 while an isothermal plasma is associated with the limit d → ∞.…”
Section: Thermodynamic Scenariosmentioning
confidence: 99%